Knowledge of text structure: A key cognitive strategy that helps primary students understand informational texts - Pérez Domínguez, Marta; Raído Brañas, Mª Dolores; Ovalle Torres, Miriam; González Sánchez, Luis; Calero Pérez, Esther; Piedra Gamidez, Ander; Calero, Andrés (Didáctica. Lengua y Literatura, 2016)
Comprehension of informational texts is essential to the academic success of every student in Primary Education, and it should be an important focus for teachers as a result of the publication of the new Primary School Curriculum (RD 126/2014, February-28th). In this paper, we will describe a Pedagogical Innovation Project carried out at the CEIP “Santa Bárbara” in Matarrosa (León) during the school year 2013/2014, with third, fourth, fifth and sixth grade elementary students. The aim was to develop their knowledge and use of the informational text structure as a key cognitive strategy that young readers have to activate in order for them to improve their reading comprehension skills. The informational text structure functions as a valuable syntactic and semantic cueing system both inside and outside the text, which informs the reader about the logical connections among its ideas, so that comprehension can be attained. Our students, aged 8 to 12, worked on a set of cognitive and metacognitive strategies throughout the school year, which helped them to understand better the meaning and use of the different types of informational texts (description, compare/contrast, sequence, cause/effect and problem/solution), to comprehend them, recall and produce written summaries of the texts read in the classroom. At the end of the academic year, the students showed significant improvement in: a) their ability to read strategically, b) their skill to produce well-structured written sentences with each of the five textual structures, c) the knowledge and use of the particular keywords that articulate the cohesion and textual organization of the five text structures they worked, d) their reading comprehension and the ability to write summaries of the different texts we read in class, and finally e) their interest in reading informational texts.